Ca2+ sensor proteins in dendritic spines: a race for Ca2+ - Raghuram, Vijeta; Sharma, Yogendra; Kreutz, Michael R. (Frontiers in Molecular Neuroscience, 2012)
Dendritic spines act as micro-compartments of Ca2+ regulation. In a recent study, it was suggested that the ubiquitous and evolutionarily conserved Ca2+ sensor, calmodulin (CaM), is the first to intercept Ca2+ entering the spine and might be responsible for the fast decay of Ca2+ transients in spines. Neuronal calcium sensor (NCS) and neuronal calcium-binding protein (nCaBP) families consist of Ca2+ sensors with largely unknown synaptic functions despite an increasing number of interaction partners. Particularly how these sensors operate in spines in the presence of CaM has not been discussed in detail before. The limited Ca2+ resources and the existence of common targets create a highly competitive environment where Ca2+ sensors compete with each other for Ca2+ and target binding. In this review, we take a simple numerical approach to put forth possible scenarios and their impact on signalling via Ca2+ sensors of the NCS and nCaBP families. We also discuss the ways in which spine geometry and properties of ion channels, their kinetics and distribution, alter the spatio-temporal aspects of Ca2+ transients in dendritic spines, whose interplay with Ca2+ sensors in turn influences the race for Ca2+.